Ajita Agada for Poisoning Conditions and Interpret its Mode of Actions: Keeerthisinghe S.M.M.D. 1and Wimalasiri Y.S.G.2 (Sri Lanka Journal of Indigenous Medicine (SLJIM), 2022)
Poisonings have been identified as critical conditions in Ayurveda since centuries. Agada tantra is the specialized clinical branch where the therapeutic roots for poison management lie. Agada are given a significance as anti-poisonous formulations in various Ayurveda treatises. Ajita agada is the main concern in this study which the references were found on Susruta Samhita Kalpasthana, Ashtanga Samgraha Uttarasthana and Bhaisajjaratnavali. This herbo-mineral anti-poisonous formulation is consisted of 17 ingredients and bee honey as its dipping material. Ajita agada is prescribed mainly for snake bites (Sarpa visha) and also for all the other kinds of animate (Jangama) and inanimate (Sthavara) poisons. Still, any organized management procedure in critical care for poisonings from Ayurveda perspective hasn’t observed included in national health care system of Sri Lanka. This study is aimed at fulfilling this lacuna by means of finding a strategy for critical care of poisonings through Ajita agada. Upon Ayurveda pharmacodynamics are concerned, it’s observed that Katu (76.47%), Tikta (35.29%) and Kashaya rasa (29.41%) are prominent Rasa, Laghu (94.11%), Tikshna (58.82%) and Ruksha guna (35.29%) are prominent Guna, Ushna (82.35%) and Katu (23.52%) as the prominent Virya and Vipaka. By virtue of pharmacodynamics, Ajita agada shows a similarity with poison itself. This is very remarkable in collective understanding the therapeutic action of Ajita agada in management of poisonings. Further, chemical and clinical studies should be conducted with this regard. Keywords: Ajita agada, Anti-toxicity, Visha, Visha upakrama.